Avaliação da qualidade físico-química e microbiológica do mel das abelhas africanizadas (Apis melliferaL.) da região Leste/RN Brasil. - Medeiros, Altevir Paula de (2011)
It has been verified the honey produced by Apis mellifera L. in the East Potiguar Mesoregion, RN, Brazil, to identify if they satisfy the specifications determined by the legislations. 90 samples have been analyzed determining the physical-chemical parameters, qualitative tests, microbiological and with some adulterations done (addition of commercial sugar and corn glucose) to check the detection limits of Lund and Lugol s tests. The samples were collected for a honey exporting company from RN and sent to UFERSA, in aliquots of 500ml and analyzed 48 hours after each collection. They were collected from January to February in 2009. The following results were obtained: moisture (15,23%±0,56%), water activity (0,61±0,02%), solids (0,04±0,02%), ashes (0,19±0,09%), acidity (31,55 meq/kg±6,67), sugar (76,61%±6,22), sucrose (4,72%±0,87), HMF (14,16 mg/kg±8,86), Lund (2,96+0,99%) and negative diastase activity. The values of moisture, HMF, sugar, free acidity, insoluble solids and ashes have been in accordance with the regulations of BRASIL (2000), Codex (2001) and MERCOSUL (CMG 89/99). The microbiological parameters analyzed were: coliform presence at 35°C and 45°C, Salmonella sp, mold and yeast quantification from the 90 samples of the collected honey. 60 samples presented a mold and yeast counting higher than 102 UFC/g above the permitted amount by MERCOSUL s legislation with the limit of 1X102 UFC/g or 100 UFC per gram. The honey samples analyzed had values higher than >1.100 NMP/g to coliforms at 35°C and 45°C and seven samples with growth between 15 and 3,6 NMP/g-1 which are considered so high, based on the legislation of MERCOSUL the maximum limit of <3 NMP/g. Two samples presented Salmonella sp that suggests the necessity of implementation of good practices in all the levels of the productive chain, especially in the apiary and the necessity of knowing the microbiota of honey in the regions of Brazil;